Q:

3x + 4y =10 6x -2y = 40

Accepted Solution

A:
Simplifying 3X + 10 = 6X + 40 Reorder the terms: 10 + 3X = 6X + 40 Reorder the terms: 10 + 3X = 40 + 6X Solving 10 + 3X = 40 + 6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6X' to each side of the equation. 10 + 3X + -6X = 40 + 6X + -6X Combine like terms: 3X + -6X = -3X 10 + -3X = 40 + 6X + -6X Combine like terms: 6X + -6X = 0 10 + -3X = 40 + 0 10 + -3X = 40 Add '-10' to each side of the equation. 10 + -10 + -3X = 40 + -10 Combine like terms: 10 + -10 = 0 0 + -3X = 40 + -10 -3X = 40 + -10 Combine like terms: 40 + -10 = 30 -3X = 30 Divide each side by '-3'. X = -10 Simplifying X = -10